Disaster Communication Representation on BNPB's Instagram as COVID-19 Response Acceleration Task Force - Lestari Nurhajati; Amanda Pramarta Putri; Xenia Angelica Wijayanto (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
Indonesia is one of the countries in Asia that has experienced a severe impact due to the COVID-19 virus. This message was conveyed by the president of Indonesia officially on March 2, 2020. The Indonesian government received various criticisms. The Indonesian people considered the government to be slow in taking a stand on this global pandemic. BNPB (National Disaster Management Agency) was then appointed as the COVID-19 Response Acceleration Task Force. As an agency engaged in disaster issues, BNPB strives to carry out the disaster mitigation process for the COVID-19 case. This study aims to determine how BNPB carries out the representation of disaster communication through Instagram @bnpb_indonesia. The disaster communication process is inseparable from disaster mitigation itself. The concept of successful disaster communication emphasizes the affected, the commitment of the leadership, communication as part of planning and operations in the field, awareness of the situation, and cooperation with the media. This study uses Barthes’s semiotic method to see how denotative, connotative, and mythical forms are formed on BNPB’s Instagram. This preliminary research shows that in general, BNPB Instagram has worked hard to fulfill its organizational profile as a representation of the foremost organization dealing with the COVID-19 disaster in Indonesia. However, in terms of successful communication, several things are not fulfilled on the existing BNPB Instagram display, especially the lack of focus on those affected.Keywords: Representation, disaster communication, covid-19, Instagram, BNPB ABSTRAKIndonesia menjadi salah satu negara di Asia yang mengalami dampak sangat serius akibat virus Covid-19. Hal ini disampaikan presiden Indonesia secara resmi pada tanggal 2 Maret 2020. Berbagai kritik dituai oleh pemerintah Indonesia, masyarakat Indonesia menganggap pemerintah lamban mengambil sikap atas pandemik global ini. BNPB (Badan Nasional Penanggulangan Bencana) kemudian ditunjuk sebagai Gugus Tugas Percepatan Penangangan Covid-19. Sebagai badan yang bergerak pada isu kebencanaan, BNPB berupaya keras melakukan proses mitigasi bencana atas kasus Covid-19. Penelitian ini bertujuan mengetahui bagaimana representasi komunikasi bencana dilakukan BNPB melalui Instagram @bnpb_indonesia. Proses komunikasi bencana tidak terpisahkan dari mitigasi bencana. Konsep keberhasilan komunikasi bencana menekankan fokus pada yang terdampak, adanya komitmen pimpinan, komunikasi sebagai bagian dari perencanaan dan operasi di lapangan, kesadaran atas situasi, serta adanya kerja sama dengan media. Penelitian ini menggunakan metodologi semiotika Barthes untuk melihat bagaimana denotatif, konotatif dan mitos terbentuk atas Instagram BNPB. Penelitian awal ini menunjukkan hasil bahwa secara umum Instagram BNPB berupaya keras memenuhi profil organisasinya sebagai representasi organisasi terdepan yang menangani bencana Covid-19 di Indonesia. Namun dari sisi keberhasilan komunikasinya, ada beberapa hal yang tidak terpenuhi pada tampilan Instagram BNPB yang ada, terutama kurang fokusnya pada yang terdampak.Kata Kunci: Representasi, komunikasi bencana, covid-19, Instagram, BNPB